Breastfeeding rates in immigrant and non‐immigrant women: A systematic review and meta‐analysis. Issue 3 (26th April 2019) - Dennis, Cindy‐Lee; Shiri, Rahman; Brown, Hilary K.; Santos, Hudson P.; Schmied, Virginia; Falah‐Hassani, Kobra
Abstract: Breastfeeding benefits mothers and infants. Although immigration in many regions has increased in the last three decades, it is unknown whether immigrant women have better breastfeeding outcomes than non‐immigrants. The aim of this study was to conduct a systematic review and meta‐analysis to determine whether breastfeeding rates differ between immigrant and non‐immigrant women. We searched Medline, Embase, PsycINFO, CINAHL and Google Scholar, 1950 to 2016. We included peer‐reviewed cross‐sectional and cohort studies of women aged ≥16 years that assessed and compared breastfeeding rates in immigrant and non‐immigrant women. Two independent reviewers extracted data using predefined standard procedures. The analysis included 29 studies representing 1, 539, 659 women from 14 countries. Immigrant women were more likely than non‐immigrants to initiate any (exclusive or partial) breastfeeding (pooled adjusted prevalence ratio 1.13, 95% confidence interval [CI] 1.07–1.19; 11 studies). Exclusive breastfeeding initiation was higher but borderline significant (adjusted prevalence ratio 1.20, 95% CI 1.00–1.45; 5 studies, p  = 0.056). Immigrant women were more likely than non‐immigrants to continue any breastfeeding between 12‐ and 24‐week postpartum (pooled adjusted risk ratio 2.04, 95% CI 1.79–2.32; 3 studies) and > 24 weeks (adjusted risk ratio 1.33, 95% CI 1.02–1.73; 6 studies) but not exclusive breastfeeding. Immigrant women are more likely than non‐immigrants to initiate and maintain any breastfeeding, but exclusive breastfeeding remains a challenge for both immigrants and non‐immigrants. Social and cultural factors need to be considered to understand the extent to which immigrant status is an independent predictor of positive breastfeeding practices.